NATURAL-ANTHROPOGENIC SYSTEMS AS AN OBJECT OF TERRITORY PLANNING - Удовиченко, Вікторія (Human Geography Journal, 2016)
“Natural-anthropogenic system” is defined in this article. Structure of natural-anthropogenic systems as an object of planning activity is carried out. The key results of natural-anthropogenic systems structuring as a complicated type of systems are under consideration by using a block model. The key blocks and integral blocks of natural-anthropogenic systems are characterized. The main system forming, attributive, hierarchical and functional linkages which exist between blocks of natural-anthropogenic systems are defined and analyzed.